2007
DOI: 10.1111/j.1524-475x.2007.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of venous leg ulcers with a laser‐based three‐dimensional method: Comparison to computer planimetry with photography

Abstract: A lack of reproducible and practical methods to assess venous leg ulcer healing is a major problem encountered by investigators evaluating various treatments. We aimed to compare a new laser-based three-dimensional (3D) measuring device with computer planimetry with photography for the assessment of venous leg ulcers, and to estimate the reliability of measurements by the methods. Sixty measurements of perimeter and area of 15 venous leg ulcers, < 10 cm in diameter (eight patients; six females; mean age 71 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 15 publications
0
29
0
1
Order By: Relevance
“…However, while several existing commercial products, notably the Aranz and Eykona systems, have a reasonable body of associated clinical evidence, the pace of technological development means the field remains rapidly changing; the authors are aware of several groups active in this area of research. 31,35,36 As yet, no system has demonstrated widespread adoption in routine clinical use.…”
Section: Resultsmentioning
confidence: 99%
“…However, while several existing commercial products, notably the Aranz and Eykona systems, have a reasonable body of associated clinical evidence, the pace of technological development means the field remains rapidly changing; the authors are aware of several groups active in this area of research. 31,35,36 As yet, no system has demonstrated widespread adoption in routine clinical use.…”
Section: Resultsmentioning
confidence: 99%
“…The wound volume was determined as the volume between the measured surface and the virtual healthy skin. In that way the medical personnel can objectively evaluate the progress of the healing, and change the course of treatment if necessary [11]. In second application the human head orientation with respect to the torso was measured.…”
Section: Results and Applicationmentioning
confidence: 99%
“…Based on these two measurements, the area of the wound is estimated as a rectangle [16] or as an ellipse [4]. When the model is a rectangle, the area may be overestimated by 10% to 45% with less accuracy for smaller wounds [16].…”
Section: Common Practices For Wound Assessmentmentioning
confidence: 99%
“…This process is time consuming and prone to human error. Alternatively, the outline could be trace directly into a digital pad [13,16,28]. Several studies have shown that the most important factor in error measurement is the correct and consistent identification of the border of the wound due its poor definition or the subjectivity of the process [7].…”
Section: Common Practices For Wound Assessmentmentioning
confidence: 99%